Development of a Problem Based Learning Oriented Movement System Module with a Computational Thinking Approach to Improve Students' Critical Thinking Skills - Karim, Maftukhatul; Setiati, Ning; Widiyaningrum, Priyantini (Journal of Innovative Science Education, 2023)
The development of a Problem Based Learning-oriented Movement System module with a Computational Thinking approach to improving students' critical thinking skills is one of the efforts to improve this pedagogic competency. The purpose of this research is to analyze the validation of problem-based learning-oriented motion system modules with a computational thinking approach to improve students' critical thinking skills and analyze the feasibility of problem-based learning-oriented motion system modules with a computational thinking approach to improve students' critical thinking skills. This study used a Research and Development (RnD) design and the technique used was a one-shot case study. The research was conducted at MAN Salatiga with 71 research subjects divided into 2 classes. The results of the study are as follows: (1) the assessment of the material by material experts obtained 85, 67%, and 76.5% with very good and good criteria, and the assessment by media experts obtained 90% and 92.00% with very good criteria so that the media declared valid. The value obtained from students who used the module and then worked on critical thinking questions obtained an average value of 92.69 after being analyzed based on the predetermined Minimum Mastery Criteria (KKM). KKM value determined namely 75. The test results showed 98.59% of students passed the very high category, So it can be stated that the use of the Movement System module oriented to Problem Based Learning with Computational Thinking is approachable to improve students' critical thinking skills.